Continuing and community education as engaged learning - Wendy M. Green; Catherine Hansman; Nancy M. Prattt; Marius Boboc (Adult Education Research Conference, 2021)
CPE providers focus on understanding learning needs, designing and providing educational offerings, and evaluating programs. Cervero and Daly believe these decisions are made within the contested spaces of the social, professional, institutional, and educational systems; however, CPE continues to focus on the needs of the workplace and economic demands. We argue for a re-framing of how CPE is conceptualized and situated within the realm of adult learning and development specific to higher education institutions which engage in the endeavor, proposing the Community Transformation Model for Continuing and Extended Education to address neo-liberalism bias.
Keywords: neoliberal ideology; continuing professional education; Community Transformation Model for Continuing and Extended Education